SHARIA GOVERNANCE AND THE CHALLENGES OF SYSTEMIC FINANCING RISK: A CRITICAL ANALYSIS OF THE DYNAMICS OF DSN-MUI FATWAS - Asep Hedi Turmudi; Syaifuddin Syaifuddin; Rusmiyanti Wontami; Samad Umarama; Abu Sanmas (Universitas Nurul Jadid, 2026)
Indonesia's Islamic finance industry faces a new challenge when the DSN-MUI fatwa, as a normative guideline, must be translated into the bank's evolving policies and operational practices. This study aims to understand how sharia actors—DSN, DPS, regulators, and bank management—experience, interpret, and manage the dynamics of fatwas in the context of systemic financing risk. Using a grounded theory approach with an emphasis on subjective experience, data is collected through in-depth interviews and observations to capture the meanings, perceptions, and dilemmas experienced by stakeholders. The findings show that the fatwa translation process is a complex social experience, characterized by negotiations of religious understanding, time asynchrony between financial innovation and fatwa response, and the interpretive burden felt by industry players when faced with regulatory gray areas. Actors portray fatwas as a guideline that gives direction, but at the same time a source of uncertainty when its application is not uniform. These dynamics shape risk vulnerabilities that are not only technical, but also psychological and institutional. This research emphasizes the importance of more responsive fatwa communication, increasing the capacity of sharia governance, and strenGraunded Theoryhening risk mitigation mechanisms based on understanding the experiences of industry players. Overall, the study provides a new perspective on how fatwas work in practice and how those dynamics affect the stability of the Islamic financial system.